Livingstonites gabrielae Gen. Et Sp. Nov., permineralized moss (Bryophyta: Bryopsida) from the aptian cerro negro formation of Livingston Island (South Shetland Islands, Antarctica) - Vera, Ezequiel Ignacio (Ameghiniana)
The Cerro Negro Formation is a non-marine succession that outcrops in Byers Peninsula (livingston Island) and Williams Point (Snow Island). Both islands belong to the South Shetland Islands Archipelago, Antarctica. 40Ar/39Ar age of the Cerro Negro Formation was estimated at 120.3 ±2.2 Ma, 119.4±0.6 Ma and 119.1±0.8 Ma (Aptian) (Ha-thway, 1997; Hathway et al., 1999). A highly diverse pal-aeoflora, containing mosses, liverworts, hepatophytes, horse-tails, ferns, corystosperms, Caytoniales, bennettites, cycads, and conifers was recorded by several authorsfrom the unit (Hernández and Azcárate, 1971; Torres et al., 1997; Césari et al., 1998, 1999, 2001; Cantrill, 2000; Falcon-lang and Cantrill, 2001; Césari 2006; Parica et al., 2007; Vera, 2007, 2009; among others). Fil: Vera, Ezequiel Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Geología. Cátedra de Paleontología; Argentina